Environmental impact of industrial sludge stabilization/solidification products: Chemical or ecotoxicological hazard evaluation? - Silva, Marcos A.R.; Testolin, Renan C.; Godinho-Castro, Alcione P.; Corrêa, Albertina X.R.; Radetski, Claudemir M. (Journal of hazardous materials, 2011)
► Nowadays, the classification of industrial solid wastes is not based on risk analysis, but only in chemical leachate constitution. ► Generated ecotoxicological data showed that the results of chemical analysis sometimes underestimate or overestimate the hazardous potential of S/S derived products. ► This is a evidence that solid (waste) classification must be made preferentially by ecotoxicity tests and policy makers must pay attention to this type of evidence. Nowadays, the classification of industrial solid wastes is not based on risk analysis, thus the aim of this study was to compare the toxicity classifications based on the chemical and ecotoxicological characterization of four industrial sludges submitted to a two-step stabilization/solidification (S/S) processes. To classify S/S products as hazardous or non-hazardous, values cited in Brazilian chemical waste regulations were adopted and compared to the results obtained with a battery of biotests (bacteria, alga and daphnids) which were carried out with soluble and leaching fractions. In some cases the hazardous potential of industrial sludge was underestimated, since the S/S products obtained from the metal-mechanics and automotive sludges were chemically classified as non-hazardous (but non-inert) when the ecotoxicity tests showed toxicity values for leaching and soluble fractions. In other cases, the environmental impact was overestimated, since the S/S products of the textile sludges were chemically classified as non-inert (but non-hazardous) while ecotoxicity tests did not reveal any effects on bacteria, daphnids and algae. From the results of the chemical and ecotoxicological analyses we concluded that: (i) current regulations related to solid waste classification based on leachability and solubility tests do not ensure reliable results with respect to environmental protection; (ii) the two-step process was very effective in terms of metal immobilization, even at higher metal-concentrations. Considering that S/S products will be subject to environmental conditions, it is of great interest to test the ecotoxicity potential of the contaminants release from these products with a view to avoiding environmental impact given the unreliability of ecotoxicological estimations originating from chemical analysis.